The Development of Web-Based Learning: Video Tutorial for Animation Technology Subject - Hamzah, Norhasyimah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Animation Technology is one of the courses that must be taken by a Creative Multimedia student at the Faculty of Technical and Vocational Education, UTHM before graduating. In this course, there are some software used for the production of animation in this course. The main software used by students is the Adobe Flash software. The Adobe Flash is a software that is often used for creating animations and integrating videos into web pages. Therefore, this study aims to design and develop a web application of practical learning video tutorial Adobe Flash to enable users to view the videos tutorial related to Adobe Flash software. Developers have been using the Hannafin and Peck Models throughout the development process of this practical learning video tutorials. In addition, there are two type of instruments that have been used in this project which are checklist forms and an expert confirmation. The checklist form is used for expert assessment for the development of practical learning video tutorials. There are three (3) experts are evaluating the functionality of Adobe Flash CS6's practical learning videos online. The findings shows that the expert assessment is based on aspects of content design, interface design and interaction design are suitable with the standard for developing web-based learning. Overall, the development of web-based learning using video tutorial for Animation Technology subject can be one of the teaching aids in teaching and learning process especially during Pandemic Covid19.